Fine Mapping and Functional Research of Key Genes for Photoperiod Sensitivity in Maize - Fei, Jianbo; Jiang, Qingping; Guo, Mingyang; Lu, Jianyu; Wang, Piwu; Liu, Siyan; Qu, Jing; Ma, Yiyong; Guan, Shuyan (Frontiers in Plant Science, 2022)
Maize is native to the tropics and is very sensitive to photoperiod. Planting in temperate regions with increased hours of daylight always leads to late flowering, sterility, leggy plants, and increased numbers of maize leaves. This phenomenon severely affects the utilization of tropical maize germplasm resources. The sensitivity to photoperiod is mainly reflected in differences in plant height (PH), ear height (EH), total leaf number (LN), leaf number under ear (LE), silking stage (SS), and anthesis stage (AT) in the same variety under different photoperiod conditions. These differences are more pronounced for varieties that are more sensitive to photoperiod. In the current study, a high-density genetic map was constructed from a recombinant inbred line (RIL) population containing 209 lines to map the quantitative trait loci (QTL) for photoperiod sensitivity of PH, EH, LN, LE, SS, and AT. A total of 39 QTL were identified, including three consistent major QTL. We identified candidate genes in the consensus major QTL region by combined analysis of transcriptome data, and after enrichment by GO and KEGG, we identified a total of four genes (Zm00001d006212, Zm00001d017241, Zm00001d047761, and Zm00001d047632) enriched in the plant circadian rhythm pathway (KEGG:04712). We analyzed the expression levels of these four genes, and the analysis results showed that there were significant differences in response under different photoperiod conditions for three of them (Zm00001d047761, Zm00001d006212 and Zm00001d017241). The results of functional verification showed that the expression patterns of genes rhythmically oscillated, which can affect the length of the hypocotyl and the development of the shoot apical meristem (SAM). We also found that the phenotypes of the positive plants were significantly different from the control plants when they overexpressed the objective gene or when it was knocked out, and the expression period, phase, and amplitude of the target gene also shifted. The objective gene changed its own rhythmic oscillation period, phase, and amplitude with the change in the photoperiod, thereby regulating the photoperiod sensitivity of maize. These results deepen our understanding of the genetic structure of photoperiod sensitivity and lay a foundation for further exploration of the regulatory mechanism of photoperiod sensitivity.